Selective Separation of Platinum in the Propyl-alcohol-Sodium Sulfate Two-phase Aqueous Extraction System - GAO†, YUNTAO; LIU*, XIAOHAI; TAO‡, YE; WANG§, JIAQIANG; WANG§, WEI; WU§, LISHANG; WANG, XIUEMEI (Asian Journal of Chemistry, 2009)
The extraction separation and phase distribution behaviours of iodidecomplexes of platinum(IV) in propyl-alcohol-sodium sulfate two-phaseaqueous extraction system have been investigated. The amount of Na2SO4added, the initial volume of propyl alcohol and the acidity of the systemare mainly factors affecting the formation and phase separation of theaqueous two-phase system. Platinum(IV) is found to be extracted intothe propyl alcohol phase due to ion pair formation of platinum(IV) as[Pt I62-·2(PrOH2+)2] in the presence of KI and HCl medium. The experimentalresults indicate that platinum can be quantitatively and highlyselectively extracted by the optimized method, using which > 99.0 %extraction efficiency can be achieved. The proposed method has beensuccessfully applied to the selective separation of platinum from samplescontaining large amount of base metals including Fe2+, Ca2+, Mg2+, Mn2+,Al3+, Pb2+ and Zn2+ in synthetic sample and exhibits high selectivity toplatinum.